Predictors of Unusual ECG Characteristics in Cavotricuspid Isthmus-Dependent Atrial Flutter Ablation - Hoffmayer, Kurt S. (2011)
BACKGROUND: An unusual 12 lead electrocardiographic pattern may be present in patients with cavotricuspid isthmus-dependent flutter. OBJECTIVE: Using baseline patient characteristics and echocardiography we sought to study predictors of unusual ECG characteristics in patients with cavotricuspid isthmus-dependent atrial flutter. METHODS: This was a dual center, retrospective cohort study of 147 patients undergoing electrophysiology study and ablation for cavotricuspid isthmus dependent atrial flutter. RESULTS: Among this cohort, 23 patients (16%) had unusual 12-lead ECG characteristics. Using multivariate logistic regression, we found two clinical predictors for having an unusual ECG pattern. A clockwise pattern at time of EPS was the strongest predictor of an unusual ECG pattern (odds ratio [OR] 15.3 (95% confidence interval [CI] 4.0–59.4, p<0.005). In addition, patients with decreased systolic function had a 3.5 greater odds (95% CI 1.1–11.5, p=0.037) of having an unusual ECG pattern. CONCLUSIONS: Our data demonstrate that among patients suffering from cavotricuspid isthmus dependent atrial flutter who are referred for ablation, 16% will have unusual ECG patterns. Patients with clockwise atrial activation and LV dysfunction have greater odds of manifesting unusual patterns by surface electrocardiogram.